Analysis of the Expected Impact of PSAK 117 Implementation on the Quality of Financial Statements in Insurance Companies - Annisa Hayu Sekar Pertiwi; Surya Raharja (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the expected impact of PSAK 117 implementation on the quality of financial statements in insurance companies, particularly in terms of relevance and reliability of accounting information. Data were collected through questionnaires distributed to finance and accounting practitioners in insurance companies, with a total of 46 respondents from various positions and work experiences. Descriptive analysis results indicate that respondents have high expectations regarding the application of PSAK 117, with average scores of 4.46 for relevance and 4.42 for reliability of financial statements. Respondents perceive that this standard can provide more accurate, complete, and transparent information, thereby supporting more precise decision-making. These findings emphasize the importance of consistent PSAK 117 implementation to enhance financial statement quality and provide a solid basis for managerial and investment decisions in insurance companies.